EDUCATIONAL TECHNOLOGIES IN BIOLOGY TEACHING: AN IMMERSIVE EXPERIENCE WITH 3D SOFTWARE - Gomes, Luzivone Lopes; Moita, Filomena Maria G. da Silva Cordeiro (Seven Editora, 2026)
This article discusses the integration of Digital Technologies in the school context and briefly shares an experience of using P3D Software in Biology teaching. The theoretical support was based on studies by Amabis (2001), BNCC (2018), Costa (2004), Lévy (2005), Moita (2006 and 2007), among others. For data collection, bibliographic research and participant observation in the computer lab were used with the use of P3D Software in Biology classes with 9th-grade students. The study revealed that with the use of educational technologies, new ways of teaching and learning are emerging, ensuring that children and young people have their learning rights in relation to understanding, using, and creating with digital resources. The use of P3D Software made teaching more attractive and immersive. Students combined 3D images of the Human Body; Numerous possibilities exist for teaching content about the Human Body, aligned with the BNCC (Brazilian National Curriculum Base), which would not be possible in a traditional classroom setting based on linear text and images.DOI: https://doi.org/10.56238/sevened2026.008-031